An Investigation Into the Role of Osteocalcin in Human Arterial Smooth Muscle Cell Calcification - Millar, Sophie A.; John, Stephen G.; McIntyre, Christopher W.; Ralevic, Vera; Anderson, Susan I.; O'Sullivan, Saoirse E. (Frontiers in Endocrinology, 2020)
Osteocalcin (OCN) is a bone-derived protein that is detected within human calcified vascular tissue. Calcification is particularly prevalent in chronic kidney disease (CKD) patients but the role of OCN in calcification, whether active or passive, has not been elucidated. Part 1: The relationship between OCN, CKD and vascular calcification was assessed in CKD patients (n=28) and age-matched controls (n=19). Part 2: In vitro, we analysed whether addition of uncarboxylated osteocalcin (ucOCN) influenced the rate or extent of vascular smooth muscle cell (VSMC) calcification. Human aortic VSMCs were cultured in control media or mineralisation inducing media (MM) containing increased phosphate with or without ucOCN (10 ng/mL or 30 ng/mL) for up to 21 days. Markers of osteogenic differentiation and calcification were determined (alkaline phosphatase [ALP] activity, total intracellular OCN, Runx2 expression, α-SMA expression, alizarin red calcium staining, and calcium quantification). Part 1 results: In our human population, calcification was present (mean age 76 years), but no differences were detected between CKD patients and controls. Plasma total OCN was increased in CKD patients compared to controls (14 ng/mL vs 9 ng/mL; p<0.05) and correlated to estimated glomerular filtration rate (p<0.05), however no relationship was detected between total OCN and calcification. Part 2 results: In vitro, ALP activity, α-SMA expression and calcium concentrations were significantly increased in MM treated VSMCs at day 21, but no effect of ucOCN was observed. Cells treated with control media+ucOCN for 21 days did not show increases in ALP activity nor calcification. In summary, although plasma total OCN was increased in CKD patients, this study did not find a relationship between OCN and calcification in CKD and non-CKD patients, and found no in vitro evidence of an active role of ucOCN in vascular calcification as assessed over 21 days. ucOCN appears not to be a mediator of vascular calcification, but further investigation is warranted.